2023
DOI: 10.1136/oemed-2022-108533
|View full text |Cite
|
Sign up to set email alerts
|

Byssinosis and lung health among cotton textile workers: baseline findings of the MultiTex trial in Karachi, Pakistan

Abstract: ObjectivesTo assess the association of exposure in cotton mills in Karachi with different definitions of byssinosis and lung health.MethodsThis cross-sectional survey took place between June 2019 and October 2020 among 2031 workers across 38 spinning and weaving mills in Karachi. Data collection involved questionnaire-based interviews, spirometry and measurements of personal exposure to inhalable dust. Byssinosis was defined using both WHO symptoms-based (work-related chest tightness), and Schilling’s criteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…In a recent study, conducted in Karachi, Pakistan, respiratory symptoms were found in 56% of the participants, the majority of whom were working in the spinning section and had been working for a longer duration (10). This can be related to the current study where the workers of the spinning and weaving section, grouped as being directly exposed to cotton dust, had higher rates of respiratory symptoms i.e.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…In a recent study, conducted in Karachi, Pakistan, respiratory symptoms were found in 56% of the participants, the majority of whom were working in the spinning section and had been working for a longer duration (10). This can be related to the current study where the workers of the spinning and weaving section, grouped as being directly exposed to cotton dust, had higher rates of respiratory symptoms i.e.…”
Section: Discussionmentioning
confidence: 59%
“…It was also observed that the weaving section had the poorest occupational safety standards and the highest levels of inhalable cotton dust. Other factors associated with these symptoms include long duration of work in ginning, spinning, and carding areas, low educational status, and not using face masks (1,10).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, subsequent work sections such as simplex, ring frame, and auto cone pose an average risk of byssinosis due to less dustiness [ 5 , 6 , 28 , 36 , 38 ]. In addition, many studies around the globe found a relationship between dust pollution and respiratory problems such as chronic cough, bronchitis, and asthma in textile workers [ 5 – 7 , 9 14 , 21 , 27 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Pakistan, evidence suggests a significant relationship between the respiratory symptoms of textile workers and their exposure to cotton dust in the workplace. Many studies have also reported moderate to high (ranging from 8 to 35%) levels of byssinosis among textile workers with a high percentage of chronic respiratory morbidities, including bronchial asthma, chronic bronchitis, tuberculosis, and other obstructive pulmonary symptoms [ 5 , 6 , 8 , 10 , 18 – 21 ]. Although a relationship exists between cotton dust and its effects on workers' health, there is a shortage of information on the economic valuation of dust pollution that directly affects workers' health, productivity, and quality of life.…”
Section: Introductionmentioning
confidence: 99%